PD-L1+ neutrophils as novel biomarkers for stage IV melanoma patients treated with nivolumab - Cristinziano, Leonardo; Modestino, Luca; Capone, Mariaelena; Madonna, Gabriele; Mallardo, Domenico; Giannarelli, Diana; D’Angelo, Grazia; Ferrara, Anne Lise; Loffredo, Stefania; Varricchi, Gilda; Vanella, Vito; Festino, Lucia; et al. (Frontiers in Immunology, 2022)
Melanoma displays a rising incidence, and the mortality associated with metastatic form remains high. Monoclonal antibodies that block programmed death (PD-1) and PD Ligand 1 (PD-L1) network have revolutionized the history of metastatic disease. PD-L1 is expressed on several immune cells and can be also expressed on human neutrophils (PMNs). The role of peripheral blood PMNs as predictive biomarkers in anti-PD-1 therapy of melanoma is largely unknown. In this study, we aimed to determine activation status and PD-L1 expression on human neutrophils as possible novel biomarkers in stage IV melanoma patients (MPs). We found that PMNs from MPs displayed an activated phenotype and increased PD-L1 levels compared to healthy controls (HCs). Patients with lower PD-L1+ PMN frequencies displayed better progression-free survival (PFS) and overall survival (OS) compared to patients with high PD-L1+ PMN frequencies. Multivariate analysis showed that PD-L1+ PMNs predicted patient outcome in BRAF wild type MP subgroup but not in BRAF mutated MPs. PD-L1+ PMN frequency emerges as a novel biomarker in stage IV BRAF wild type MPs undergoing anti-PD-1 immunotherapy. Our findings suggest further evaluation of the role of neutrophil subsets and their mediators in melanoma patients undergoing immunotherapy.